Economics for Life Real-World Financial Literacy - Wargo, Donald T. (North Broad Press, 2023)
America has evolved into an ownership society. Home-buying decisions, resource allocation, debt exposure, and financial planning for the future are now left to individuals, with little guidance from the companies or institutions they work for. Economics, with its insistence on quantifying ideas and putting specific quantitative values on all manner of phenomena, can help us sort through many puzzling dilemmas. Economics for Life: Real-World Financial Literacy is designed to help soon-to-be college graduates emerge into the start of their "real lives" with better comprehension of how to analyze the financial decisions that they will soon have to make. Written in an easy-to-read, conversational style, this textbook will help students learn how to make decisions on saving and investing for retirement, buying a car, buying a home, as well as how to safely navigate the use of debt and credit cards.